Halantas sebagai Media Pembelajaran untuk Meningkatkan Pemahaman Tertib Berlalu Lintas - Prayitno, Prayitno (Jurnal Didaktika Pendidikan Dasar, 2018)
Pancasila State Ideology and citizenship play important roles in developing citizens with good characters including traffic disciplinary behaviors. The research objective was to improve children’s diciplines in traffic regulation in public Elementary School Tanjung 1 at Bangkalan. Halantas is an educative play combining halma and traffic rules. A classroom action research was conducted using qualitative method. Quantitative data were gathered on four aspects, namely: comprehension, strategy, creative thinking, and honest attitude. The research result shows that Halantas play could improve children’s understanding on traffic rules.